Prosaposin deficiency and saposin B deficiency (activator-deficient metachromatic leukodystrophy): report on two patients detected by analysis of urinary sphingolipids and carrying novel PSAP gene mutations - Kuchar, Ladislav; Ledvinová, Jana; Hrebícek, Martin; Mysková, Helena; Dvoráková, Lenka; Berná, Linda; Chrastina, Petr; Asfaw, Befekadu; Elleder, Milan; Petermöller, Margret; Mayrhofer, Heidi; Staudt, Martin; et al. (American journal of medical genetics. Part A, 2009)
Prosaposin deficiency (pSap-d) and saposin B deficiency (SapB-d) are both lipid storage disorders caused by mutations in the PSAP gene that codes for the 65-70 kDa prosaposin protein, which is the precursor for four sphingolipid activator proteins, saposins A-D. We report on two new patients with PSAP gene defects; one, with pSap-d, who had a severe neurovisceral dystrophy and died as a neonate, and the other with SapB-d, who presented with a metachromatic leukodystrophy-like disorder but had normal arylsulfatase activity. Screening for urinary sphingolipids was crucial to the diagnosis of both patients, with electrospray ionization tandem mass spectrometry also providing quantification. The pSap-d patient is the first case with this condition where urinary sphingolipids have been investigated. Multiple sphingolipids were elevated, with globotriaosylceramide showing the greatest increase. Both patients had novel mutations in the PSAP gene. The pSap-d patient was homozygous for a splice-acceptor site mutation two bases upstream of exon 10. This mutation led to a premature stop codon and yielded low levels of transcript. The SapB-d patient was a compound heterozygote with a splice-acceptor site variant exclusively affecting the SapB domain on one allele, and a 2 bp deletion leading to a null, that is, pSap-d mutation, on the other allele. Phenotypically, pSap-d is a relatively uniform disease of the neonate, whereas SapB-d is heterogeneous with a spectrum similar to that in metachromatic leukodystrophy. The possible existence of genotypes and phenotypes intermediate between those of pSap-d and the single saposin deficiencies is speculated.
Keywords: Sequence Deletion; Infant; mozek; předškolní dítě; Humans; Brain; Magnetic Resonance Imaging; Mutation; kůže; sekvenční delece; Codon, Nonsense; magnetická rezonanční tomografie; Sphingolipids; mužské pohlaví; Skin; nesmyslný kodon; Child, Preschool; metachromatická leukodystrofie; heterozygot; Infant, Newborn; místa sestřihu RNA; Leukodystrophy, Metachromatic; Homozygote; mutační analýza DNA; Saposins; novorozenec; DNA Mutational Analysis; homozygot; lidé; Heterozygote; dítě; Child; mutace; sfingolipidy; Male; saposiny; kojenec; RNA Splice Sites